Pengaruh Model Direct Instruction terhadap Kemampuan Teknik Dasar Memainkan Alat Musik Hadrah pada Siswa Disabilitas Netra Kelas X - Dandi, Dandi; Prystiananta, Nostalgianti Citra; Mais, Asrorul (JOEAI (Journal of Education and Instruction), 2025)
This study investigates the impact of the direct instruction model on the basic technical skills of playing the hadrah instrument among tenth-grade blind students at the Branjangan State Special Needs School in Jember. This study employed a quantitative experimental method with a "one-group pre-test post-test design." The purpose of this method was to evaluate the impact of the treatment provided by the researcher, as observed in the results obtained by comparing the conditions before and after the treatment. The sample of this study consisted of two tenth-grade blind students at the Branjangan State Special Needs School in Jember, selected using purposive sampling based on specific criteria. The results of this study indicate that blind students possess the basic technical skills necessary for playing the hadrah instrument, as evidenced by an initial pre-test score of 25%, which increased significantly after the implementation of the Direct Instruction model to 79.5%. The post-test score also increased by approximately 68%. In conclusion, the direct instruction model for teaching the basic technical skills of playing the hadrah instrument to tenth-grade blind students at the Branjangan State Special Needs School in Jember can improve their ability and expertise in understanding and mastering the lessons taught.   Keywords: Direct Instruction Model, Students with Visual Disabilities, Basic Technical Skills in Playing the Hadrah Musical Instrument